Α1-adrenoceptor ligands inhibit chemokine receptor heteromerization partners of α1B/D-adrenoceptors via interference with heteromer formation. (April 2023) - Gao, Xianlong; Enten, Garrett A.; McGee, Michelle Y.; Weche, McWayne; Majetschak, Matthias
Abstract: We reported previously that α1 -adrenoceptor (α1 -AR) ligands inhibit chemokine receptor (CR) heteromerization partners of α1B/D -AR. The underlying mechanisms are unknown and in vivo evidence for such effects is missing. Utilizing CCR2 and α1B -AR as prototypical partners, we observed in recombinant systems and THP-1 cells that α1B -AR enhanced whereas its absence inhibited Gαi signaling of CCR2. Phenylephrine and phentolamine reduced the CCR2:α1B -AR heteromerization propensity and inhibited Gαi signaling of CCR2. Phenylephrine cross-recruited β-arrestin-2 to CCR2, and reduced expression of α1B/D -AR, CR partners (CCR1/2, CXCR4) and corresponding heteromers. Phentolamine reduced CR:α1B/D -AR heteromers without affecting β-arrestin-2 recruitment or receptor expression. Phenylephrine/phentolamine prevented leukocyte infiltration mediated via CR heteromerization partners in a murine air pouch model. Our findings document that α1 -AR ligands inhibit leukocyte migration mediated by CR heteromerization partners in vivo and suggest interference with α1B -AR:CR heteromerization as a mechanism by which CR partners are inhibited. These findings provide new insights into the pharmacology of GPCR heteromers and indicate that an agonist and antagonist at one GPCR can act as antagonists at heteromerization partners of their target receptors. Graphical Abstract: ga1